Histologic and Histomorphometric Evaluation of Implant Osseointegration of a Dental Implant Three Years in Function Removed Due to Abutment Fracture - Cameron, Y. S. Lee; Hari, Prasad; Sanjana, Prasad; Jon, B. Suzuki (Journal of Dentistry And Oral Implants, 2026)
For the edentulous patient, dental implant therapy is the accepted treatment to replace one or more missing teeth as implant survival rates are greater than 90%. Unfortunately, surgical removal of dental implants occurs for a variety of reasons. As human studies are limited, this case report provides an opportunity to evaluate the peri-implant characteristics in a dental implant removed from a patient using histology. In our patient, the implant was removed three years after completion of the prosthetic phase due to fracture of the abutment that could not be removed from the implant. Histological examination of the implant revealed mature lamellar bone in direct contact with the implant surface. Histomorphometric evaluation revealed a bone-to-implant contact (BIC) of 73.6%.
Keywords: Histologic evaluation; Histomorphometric analysis; Implant osseointegration; Bone-to-implant-contact (BIC)